2015
DOI: 10.21273/hortsci.50.9.1365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Treatments on Cut Flower Opening and Senescence in Wintersweet (Chimonanthus praecox)

Abstract: Wintersweet (Chimonanthus praecox) is a woody garden plant with fragrant flowers, which blooms in deep winter. The vase life of fresh cut flowers is 8–9 days. We applied ethylene and 1-methylcyclopropene (1-MCP; an ethylene action inhibitor) to test the role of ethylene in flower opening and senescence. In addition, abscisic acid (ABA), gibberellic acid (GA3), two cytokinins, 6-benzylaminopurine (6-BA), and zeatin (ZT) were also applied. The expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Additionally, for ornamental plants and cut flowers, the research on senescence is always one of the hot issues, which is closely related to its commercial value and market competitiveness [6]. In recent years, Sui et al [7] reported the effects of hormones on the wintersweet cut flower senescence. However, little information is available regarding the molecular mechanisms of wintersweet senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for ornamental plants and cut flowers, the research on senescence is always one of the hot issues, which is closely related to its commercial value and market competitiveness [6]. In recent years, Sui et al [7] reported the effects of hormones on the wintersweet cut flower senescence. However, little information is available regarding the molecular mechanisms of wintersweet senescence.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that exogenous application of cytokinins improve the postharvest life of various cut flowers like Lilium, Dianthus, Nelumbo, Gerbera, Iris, Hemerocallis (Macnish et al 2010a;Imsabai and van Doorn 2013;Reid and Wu 2018). The role of endogenous and exogenously applied cytokinins has been studied at transgenic level in some flowers like Petunia, Nicotiana, Chimonanthus, Rosa and Dianthus (Mor et al 1983;Trivellini et al 2014;Sui et al 2015). Although both classes of cytokinins (adenine type and phenyl urea derivatives) proved effective in improving postharvest performance of cut flowers, yet the effect of thidiazuron was more promising.…”
Section: Introductionmentioning
confidence: 99%
“…The contraction of an SRG1 annotated gene family in J. hindsii could be related to phenology differences. The abscisic acid (ABA) and ethylene induced (Sui et al 2015) zinc-finger transcription factor, SRG1 has been implicated in leaf senescence in Arabidopsis (Callard et al 1996, Cui et al 2018) and fruit ripening in strawberry (Chen et al 2016). Discovering additional contractions (and expansions) in phenology-related gene families between closely related species might set a natural experiment for establishing the genetic signatures correlated with species susceptible to climate change-associated fitness loss.…”
Section: Discussionmentioning
confidence: 99%